Labor of love : gestational surrogacy and the work of making babies - Jacobson, Heather (New Brunswick, New Jersey : Rutgers University Press, 2016)
Drawn from extensive interviews with paid gestational surrogates, women employed to carry children who are not genetically their own, Labor of Love reveals the challenges they face as they deal with complicated medical procedures, delicate work-family balances, and tricky social dynamics. The book demonstrates the extent to which advances in reproductive technology are affecting all Americans, changing how we think about maternity, family, and the labor involved in giving birth.
Conceptions -- Making reproduction profitable: the contemporary surrogacy market -- Laboring to conceive: surrogacy as work -- Managing relations: surrogates and their IPs -- Working from home: surrogates and their families -- Obscured labor.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 17, 2016).
JSTOR
Keywords: Surrogate motherhood; Surrogate mothers; Human reproductive technology -- Social aspects; Families; Gestational Carriers; Mères porteuses; Procréation médicalement assistée -- Aspect social; Familles; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; MEDICAL -- Reproductive Medicine & Technology; Families; Human reproductive technology -- Social aspects; Surrogate motherhood; Surrogate mothers